Nutritional interventions for the prevention of cognitive impairment and dementia in developing economies in East-Asia: a systematic review and meta-analysis. Issue 7 (12th April 2022) - McGrattan, Andrea; van Aller, Carla; Narytnyk, Alla; Reidpath, Daniel; Keage, Hannah; Mohan, Devi; Su, Tin Tin; Stephan, Blossom; Robinson, Louise; Siervo, Mario
Abstract: Dementia represents a key impending global health challenge. The aim of this systematic review was to evaluate the current evidence on nutritional interventions for the prevention of dementia in developing economies in East-Asia. Four comprehensive databases were searched from inception until January 2020: MEDLINE, Embase, PsycInfo, and Scopus. The search was restricted to randomized controlled trials [RCTs] in adult humans, assessing the effect of nutritional interventions on global and domain specific cognitive performance and dementia risk. Meta-analysis of data was conducted for each domain and sub-categorized according to the type of nutritional intervention. Twenty-four RCTs were included, of which, fifteen studies showed significant beneficial effects on cognition. Eighteen studies were included in the meta-analysis. Significant beneficial effects were found for essential fatty acids (EPA/DHA) and micronutrient supplementation on specific cognitive domains including attention and orientation, perception, verbal functions and language skills. The effect size of the interventions appeared to be greater in older subjects with cognitive impairment. Supplementation with B-vitamins and essential fatty acids may represent promising strategies to minimize age-related cognitive decline in Asian populations. Large, high-quality, long-term trials are needed to confirm these findings.